Inhibition of Bifidobacterium Cell Wall 51.74 kDa Adhesin Isolated from Infants Feces Towards Adhesion of Enteric Phatogen E. Coli on Enterocyte Balb/C Mice - Sukrama, I D. M. (BALI MEDICAL JOURNAL, 2013)
Objectives: To determine 51.74 kDa adhesin of Bifidobacterium sp cell wall isolated from infants feces as an anti adhesion of E. coli on enterocyte mice. Methods : Randomized Posttest-Only Control Group Design was employed to investigate adherence ability of this adhesin towards E.coli adhesion on mice entherocyte. Results: In this research, it was obtained, that the 51.74 kDa adhesin cell wall of Bifidobacterium sp has an ability to inhibit adhesion of E. coli on mice enterocyte. The ability was increased as an increase of adhsein concentration. Conclusions : that can be drawn from this research is the finding of 51.74 kDa adhesin cell wall of Bifidobacterium sp isolated from infants feces that can inhibit adhseion of E. coli on mice enterocyte. Future work that can be carried out are further researches concerning whether these protein can be applied to inhibit adherence of other pathogen bacteria.
Keywords: diarrhea, adhesion, E. coli, Bifidobacterium sp.